Ultralow thermal conductivity of BaAg2SnSe4 and the effect of doping by Ga and In. (June 2019) - Li, Y.; Li, Z.; Zhang, C.; Yang, D.; Liu, T.; Yan, Y.; Liu, W.; Tan, G.; Su, X.; Uher, C.; Tang, X.
Abstract: We report on investigations of transport properties of BaAg2 SnSe4 and the effect of Ga and In doping in the structure. The experimental work is supported by calculations of the electronic band structure and phonon dispersion relations. The thermal conductivity of BaAg2 SnSe4 is exceptionally low with a value of 0.50 Wm −1 K −1 at 300 K and decreasing to 0.26 Wm −1 K −1 at 723 K. Phonon spectral calculations and low-temperature heat capacity reveal enhanced atomic displacement parameters (rattling behavior) of Ag and Se atoms in the structure. Acoustic phonons tend to flatten rather rapidly and, at 1 THz, are cut off by low-lying optic phonon modes, resulting in a suppression of the maximum Debye frequency over the first Brillouin zone. Weak chemical bonding, particularly of Ag and Se, gives rise to softened phonon modes and low speed of sound. Band structure calculations indicate that the conduction band edge is formed mainly by contributions of Se p orbitals and Sn s orbitals, while the valence band edge is dominated by contributions of Ag d orbitals and Se p orbitals. Doping with Ga or In on the site of Sn increases the room temperature carrier concentration from 4.9 × 10 16 cm −3 for BaAg2 SnSe4 to 7.8 × 10 17 cm −3 for BaAg2 Ga0.009 Sn0.991 Se4 . The power factor is greatly improved from 35 μW m −1 K −2 for pristine BaAg2 SnSe4 to 121.1 μW m −1 K −2 at 623 K for BaAg2 Ga0.009 Sn0.991 Se4 sample. A combination of the intrinsically ultralow thermal conductivity and the substantially enhanced power factor results in a peak ZT = 0.25 at 673 K for BaAg2 Ga0.002 Sn0.998 Se4 . Although this value represents a 2.5 times improvement over the figure of merit of pristine BaAg2 SnSe4, it remains rather low on account of very low carrier concentration observed even in doped samples. Graphical abstract: Image 1 Highlights: A combination of the rattling behavior of Ag and Se atoms and the weak chemical bonding feature in the structure enables an ultralow thermal conductivity of BaAg2 SnSe4 . We report on the effect of Ga and In doping in the structure. The maximum ZT of 0.25 is achieved at 673 K for BaAg2 Ga0.002 Sn0.998 Se4, being 2.5 times larger than the ZT value of pristine BaAg2 SnSe4 .